Sistem Manajemen Talenta terhadap Organisasi Pembelajar dan Keterikatan Karyawan pada PT Hipernet Indodata Kantor Pusat - Ridwan Maronrong; Adeline Amara Arina; Muhammad Ramaditya; Faris Faruqi (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2022)
This study aims to determine the effect of talent management on the formation of a learning organization and employee engagement at PT Hipernet Indodata head office. There were 60 employees participated as the samples. which data was collected using a questionnaire. The statistical analysis technique used is Path Analysis with smartPLS 3.0 program. The results showed that Talent Attraction has a significant positive effect on Learning Organization, Talent Development has an insignificant negative effect on Learning Organization, Talent Retention has a significant positive effect on Learning Organization, Talent Attraction has no significant positive effect on Employee Engagement, Talent Development has insignificant negative effect on Employee Engagement, Talent Retention has a significant positive effect on Employee Engagement, Talent Attraction has no significant positive effect on Employee Engagement through Learning Organization, Talent Development has no negative effect significant impact on Employee Engagement through Learning Organization, Talent Retention has no significant positive effect on Employee Engagement through Learning Organization.